Inclusive Disability Empowerment: Utilization of Digital Applications in Accessing Information for People With Disabilities - Pudrianisa, Sheila Lestari Giza; Astari, Devi Wening; Agustina, Dwi Pela (Universitas Ahmad Dahlan, 2024)
Digital inclusion is one of the initiatives by the Telecommunication and Information Accessibility Agency under the Ministry of Communication and Informatics. It aims to ensure that all individuals can easily access digital technology and the internet. However, digital inclusion has not been fully realized, particularly in terms of providing digital information access for people with disabilities. The purpose of this Digital Accessibility Study for Empowering Disability Inclusion is to examine the significance of digital information accessibility as a crucial factor in enhancing the inclusion and empowerment of individuals with disabilities. This study emphasizes the use of digital technology to improve information accessibility, thereby fostering independence among people with disabilities. It also aims to identify the obstacles and challenges these individuals face in achieving equal access to digital information. Utilizing qualitative descriptive methods, data for the study was collected through observations and Focus Group Discussions (FGDs) with the disability community, as well as through documentation. The findings indicate that the accessibility of information through digital applications has begun to show positive effects, particularly for individuals who are deaf or blind. Applications such as TalkBack, VoiceOver, Cash Reader, Be My Eyes, Voluntary, Infusion, Special Help, WhatsApp, Facebook, Instagram, and others, along with specialized hardware, contribute to the independence of people with disabilities. However, while information can be accessed, it remains insufficiently friendly to all disabilities. Both deaf and blind participants expressed that governmental support needs more emphasis, and they highlighted the necessity for enhanced social support from family, friends, and the community to help bridge the gap for individuals with disabilities.